Labor relations aspects of industrial medicine. [Ed. by] W.A. Toomey. [Contribs of L.J. Wade, Th.F. Nolan, F.A. van Atta a.o.] (New York State School of Industrial and Labor Relations)
Repr.: Industrial medicine and surgery, 1960, 29:2, 53-92, February.